The rights of the evicted versus the evictor : a critical analysis of the prevention of illegal eviction from and unlawful occupation of land Act 19 of 1998. moving towards a permanent housing in South Africa - Nkwinika, Rishongile Corrinne Lynn (My University, 2021)
South Africa is a country with a past characterised by extreme racial imbalances, and that is the apartheid era. After the apartheid era was dismantled and came crumbling down, South Africa adopted what the courts later described as a ‘transformative constitutionalism’. This was because the country adopted a constitution aimed at striking a balance amongst the lives of the group of citizens who were racially side-lined during the apartheid era. Similarly, the South African government derives its power from the Constitution, thereby defining its democracy through constitutionalism. The Bill of Rights in the Constitution shows the utmost regard and respect that South Africa has for human rights. The inclusion of the right to adequate housing and its underlying provision against eviction and the property right symbolised a significant step that the country was undertaking to engage social justice for all the citizens. Furthermore, the legislature has gone further to enact legislation that gives effect to the protection and realisation of the right to adequate housing. In an attempt to achieve social justice, the adopted Constitution provides the most fundamental socio-economic rights, including the right to housing. This right aims to elevate the most vulnerable citizens in the country who may not afford a decent house or shelter. However, it is apparent that the relief intended by the right to housing is not always readily achieved; most citizens still live in dire housing conditions. Case laws show that citizens in this situation resort to other unofficial means, such as occupying private land illegally to secure better settlement conditions. Coupled with the right to housing is the provision that protects the citizens from being arbitrarily evicted from any shelter they consider as their home. In the backdrop of this, the courts were, however, constantly faced with multitudes of the application calling for eviction orders against people who had illegally occupied properties belonging to other people. The consequence of this situation led to the promulgation of the PIE Act, which aims to protect the rights of both the unlawful occupier and the owner of the occupied property. No right in the Constitution may be exercised, read and interpreted to the obvious detriment of the other rights in the same Constitution. There is a conundrum that the courts and the government have to deal with; regarding the protection of the rights of property owners and unlawful occupiers. In most instances, homeless people were once owners of specific shelters or safely put on the land. Notwithstanding that the government is responsible for providing adequate housing within its reasonable legislative and other measures, issues such as over-population are preceded by homelessness. In other words, the issue of unlawful occupation affects the lawful owners and the entire country as a whole. As a result, the government must have due regard to providing a proper and alternative shelter to unlawful occupiers and homeless citizens to do away with over-population issues and have people occupying non-residential areas. This study will show that legislation can cure all forms of social problems the country encounters. However, that implementation as the life-blood of legislation should be affected by relevant state organs.
Thesis (LLM. (Development and Management Law)) -- University of Limpopo, 2021
Keywords: Racial imbalances; Human rights; Evictions; Prevention of illegal evictions; Unlawful of occupation of land; Evictions -- South Africa; Harassment -- Law and legislation -- South Africa; South Africa -- Law and legislation; Squarters -- Legal status, laws -- South Africa